When is excision necessary for atypical lobular hyperplasia and lobular carcinoma in situ?. (March 2014) - Rendi, Mara H
SUMMARY This management perspective briefly covers the histology and molecular features of lobular in situ neoplasia and provides an in-depth discussion of the need for surgical excision if lobular in situ neoplasia is diagnosed on core-needle biopsy. The management of lobular in situ neoplasia found on core-needle biopsy has been an area of recent study with varying results. Emerging data suggest that low-risk patients with a limited extent of isolated classic lobular in situ neoplasia found on core-needle biopsy may not require subsequent surgical excision. However, high-risk patients, those with extensive lobular in situ neoplasia, or other high-risk lesions noted on core-needle biopsy likely benefit from surgical excision. Most authors recommend surgical excision when pleomorphic lobular carcinoma in situ is found on core-needle biopsy due to its higher association with invasive carcinoma. However, the natural history of this more recently described variant of lobular carcinoma in situ is not fully defined, and the clinical management of pleomorphic lobular carcinoma in situ on excisional biopsy is yet to be determined.